GLOBALISASI EKONOMI DAN PENGANGGURAN: STUDI KASUS INDONESIA - Setyawan, Ari; Suparta, I Wayan; Aida, Neli (Fakultas Ekonomi dan Bisnis, UNTAN, 2021)
ABSTRACTThis study aims to examine the effect of economic globalization on the unemployment rate in Indonesia and the relationship of other macroeconomic variables such as economic growth, inflation rate, and real wage with unemployment. The data used is in the form of annual time series data from 1986 to 2018, whose research results are analyzed using the ARDL method. This study concludes that economic globalization can reduce the unemployment rate in Indonesia in the short term, although in the long term, it increases the unemployment rate. Economic growth and inflation in the short and long term have not been able to reduce the current unemployment rate, while the increase in real wages has reduced the unemployment rate in the short term, although not in the long term. By looking at these results, we need to be wary of economic globalization because economic globalization has a destructive impact in the long term. So that concrete and consistent efforts are needed from the government, the private sector, and other stakeholders so that Indonesia gets the maximum benefit from economic globalization, especially in job creation and reducing unemployment.JEL : B22, E22.Keywords : unemployment, economic globalization, economic growth, inflation, real wages. ABSTRAKPenelitian ini bertujuan melihat pengaruh tingkat globalisasi ekonomi terhadap tingkat pengangguran di Indonesia serta hubungan variabel makroekonomi lain seperti tingkat pertumbuhan ekonomi, tingkat inflasi dan tingkat upah riil dengan tingkat pengangguran. Data yang dipergunakan berupa data time series tahunan dari periode 1986 hingga 2018 yang hasil penelitiannya dianalisis menggunakan metode ARDL. Kesimpulan penelitian ini yaitu globalisasi ekonomi mampu mengurangi tingkat pengangguran di Indonesia dalam jangka pendek meskipun dalam jangka panjang malah meningkatkan tingkat pengangguran. Pertumbuhan ekonomi dan inflasi baik dalam jangka pendek dan jangka panjangnya belum mampu menurunkan tingkat pengangguran yang ada sedangkan naiknya upah riil mampu menurunkan tingkat pengangguran dalam jangka pendek meskipun tidak dalam jangka panjang. Dengan melihat hasil ini, kita perlu waspada terhadap globalisasi ekonomi karena globalisasi ekonomi ini memiliki dampak buruk dalam jangka panjang sehingga dibutuhkan upaya kongkrit dan konsisten baik dari pemerintah, swasta maupun para stakeholder lain agar Indonesia memperoleh manfaat yang sebesar-besarnya dari globalisasi ekonomi khusunya dalam upaya penciptaan lapangan kerja dan mengurangi pengangguran.